(untitled) - FAO (Rome, Italy, 2000)
This book evaluates veterinary drug residues in food. It also provides information on chemical identify, properties, use, pharmacokinetics, metabolism, tissue residue depletion of and analytical methods for the substances indicated on the cover.
Keywords: drug residues - analysis,drug therapy - veterinary,food contamination,food industry and trade